2021
DOI: 10.3390/land10090896
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Distribution Characteristics of the Cultivated Land Quality in the Diluvial Fan Terrain of the Arid Region: A Case Study of Jimsar County, Xinjiang, China

Abstract: Environmental constraints are not only important aspects that affect the cultivated land quality but also necessary factors that shall be considered when evaluating the cultivated land quality scientifically. Moreover, identifying the quality condition of cultivated land accurately is the premise for guaranteeing food security. Based on the case study of diluvial fan terrain in Jimsar County, Xinjiang in the arid region of Northwest China, this study utilizes a geographic information system spatial analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…This result indicates that model performance can be further improved by building samples with large, cultivated land patches as units. Sheng et al evaluated the quality of cultivated land on the alluvial fan in Jimusar County, Xinjiang, China, based on different cultivated land evaluation units and found that when large areas of cultivated land were used as the evaluation units for CLQ, the evaluation result was accurate [31]. The reason may be that a large area of cultivated land is more representative of the characteristics of CLQ.…”
Section: Effect Of the Sample Construction Methods On The Model Predi...mentioning
confidence: 99%
See 2 more Smart Citations
“…This result indicates that model performance can be further improved by building samples with large, cultivated land patches as units. Sheng et al evaluated the quality of cultivated land on the alluvial fan in Jimusar County, Xinjiang, China, based on different cultivated land evaluation units and found that when large areas of cultivated land were used as the evaluation units for CLQ, the evaluation result was accurate [31]. The reason may be that a large area of cultivated land is more representative of the characteristics of CLQ.…”
Section: Effect Of the Sample Construction Methods On The Model Predi...mentioning
confidence: 99%
“…In this study, the proposed ASP sample construction method further improved the accuracy of predicting CLQ using machine learning. A rapid and efficient CLQ evaluation method can provide a timely and accurate basis for orderly demarcation of permanent basic farmland, occupation or protection compensation of cultivated land, and calculation of compensation for expropriation of land [31]. Furthermore, land use planning and land reclamation planning can manage cultivated land differently, according to the spatial distribution of CLQ grade [58].…”
Section: Implications For Policy and Decision Makingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some fruits can destroy the original soil structure of cultivated land and reduce the quality of cultivated land, but it is relatively easy to restore cultivated land fertility. However, if the cultivated land is used for the production of fast-growing trees, such as poplar, or other types of economic trees with developed root systems, soil degradation, e.g., soil compaction and acidification, often arises because the trees absorb water and fertilizers during long-term planting [27][28][29][30][31][32]. Digging ponds and breeding fish in many areas completely removes the cultivated layer of arable land.…”
Section: Impact Of Ngp On Food Securitymentioning
confidence: 99%
“…The CLQ evaluation at the field scale has higher accuracy and greater diversity of indicators, and thus, can better detect the changes in CLQ factors [35], which is conducive to the fine and differentiated management of cultivated land and meets the work needs of CLBP. The recent indicator systems of CLQ evaluation at the field scale are generally based on the physical, chemical, and biological aspects of the land and are used to explore the input-output efficiency of the field [36], the soil nutrient dynamics [37], and cultivated land effects on crops [38]. However, this assessment system, which focuses on determining soil fertility, obviously lacks in-depth research on the constituent elements, operation processes, and functions of the cultivated land system, and cannot fully consider the natural, economic, and ecological conditions of the cultivated land [39].…”
Section: Introductionmentioning
confidence: 99%